Conférence: «Culture de mort / Culture de vie: Idéologie du genre en Colombie» - Anctil Avoine, Priscyll (2020)
Conférence intitulée « ''Culture de mort'' / ''Culture de vie'' : ''Idéologie du genre'' en Colombie » donnée par Priscyll Anctil Avoine, doctorante en science politique avec concentration en études féministes à l’Université du Québec à Montréal, dans le cadre du panel « Antiféminismes en Amérique latine : les cas du Brésil et de la Colombie » organisé le 21 février 2020 à l'UQAM par le Réseau québécois en études féministes (RéQEF), en collaboration avec l'Institut de recherches et d'études féministes de l'UQAM (IREF), le Réseau d'études latino-américaines de Montréal (RÉLAM) le Réseau d'études latino-américaines de Montréal (RÉLAM) et le Groupe de recherche en études féministes en science politique de l'UQAM (GREF).
Keywords: LGBTQIA2+; amérique latine; amériques; antiféminisme; approches et analyses; avortement; colombie; discours dominant; genre; identités LGBTQIA2+; justice reproductive; privilèges; régions géographiques; systèmes d'oppressions; thématiques

L'amour conjugal sous l'angle sociologique: des pratiques à la théorie - Belleau, Hélène; Piazzesi, Chiara; Seery, Annabelle (Institut national de la recherche scientifique, 2020)
Cet article propose une réflexion sociologique sur l’amour conjugal contemporain d’un point de vue théorique et empirique. À partir de données recueillies sur les arrangements financiers de personnes vivant en couple et de la littérature sociologique sur l’amour, les auteures dégagent une sémantique de la conjugalité contemporaine illustrée par huit « règles de sens », mobilisées par les acteurs pour répondre aux défis des relations intimes. L’analyse permet d’observer les décalages entre différentes logiques amoureuses d’une part, et de l’autre entre les logiques de l’amour et les réalités sociales. Les propos des conjoints révèlent l’intégration d’éléments qui tiennent de logiques divergentes dans un même univers de sens : des règles de sens favorisant l’idéalisation mythique conjuguées à celles organisées autour des images du travail sur la relation, de la communication thérapeutique et de la prise en charge entrepreneuriale de la relation. Cette analyse empirique conduit les auteures à cerner une double confusion dans la littérature contemporaine sur l’amour et les couples.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; corps; couple; cours; discipline; famille; hétérosexualité; inégalités; premier cycle; privilèges; périodes historiques; québec; relations amoureuses; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques

L’intervention psychosociale artistique: les arts pour intervenir avec les individus et les groupes - Bourassa-Dansereau, Caterine; G.-Langlois, Maxime; Robert, François P. (Nouvelles pratiques sociales, 2020)
L’intervention psychosociale utilisant les arts pour intervenir avec des individus et des groupes permet d’entrer en relation avec les personnes « autrement ». L’objectif de cet article est de présenter l’intervention psychosociale artistique comme un moyen favorisant l’atteinte d’une justice sociale pour les groupes et populations marginalisés, précarisés ou oppressés. Pour ce faire, nous proposons d’abord un tour d’horizon théorique et posons quelques assises de l’intervention psychosociale artistique au Québec. Nous présentons ensuite trois objectifs d’intervention y étant associés : la prise de parole, l’acte réflexif et la prise de conscience des dimensions collectives des expériences individuelles. Par cet article, l’autrice et les auteurs désirent présenter les nombreux apports de ce type de pratique et en souligner le caractère novateur.
Keywords: OFDIG; approches et analyses; arts visuels et médiatiques; communication; discipline; intervention; marginalisation; privilèges; pédagogie; ressource en ligne; systèmes d'oppressions; thématiques

Data feminism - D'Ignazio, Catherine; Klein, Lauren F. (ideas series, 2020)
"A new way of thinking about data science and data ethics that is informed by the ideas of intersectional feminism. Today, data science is a form of power. It has been used to expose injustice, improve health outcomes, and topple governments. But it has also been used to discriminate, police, and surveil. This potential for good, on the one hand, and harm, on the other, makes it essential to ask: Data science by whom? Data science for whom? Data science with whose interests in mind? The narratives around big data and data science are overwhelmingly white, male, and techno-heroic. In Data Feminism, Catherine D'Ignazio and Lauren Klein present a new way of thinking about data science and data ethics--one that is informed by intersectional feminist thought. Illustrating data feminism in action, D'Ignazio and Klein show how challenges to the male/female binary can help challenge other hierarchical (and empirically wrong) classification systems. They explain how, for example, an understanding of emotion can expand our ideas about effective data visualization, and how the concept of invisible labor can expose the significant human efforts required by our automated systems. And they show why the data never, ever 'speak for themselves.' Data Feminism offers strategies for data scientists seeking to learn how feminism can help them work toward justice, and for feminists who want to focus their efforts on the growing field of data science. But Data Feminism is about much more than gender. It is about power, about who has it and who doesn't, and about how those differentials of power can be challenged and changed."-
Keywords: approches et analyses; discipline; données scientifiques; histoire et politique; intersectionnalité; patriarcat; privilèges; projet charge mentale; pédagogie; racisme; rapports de pouvoir; ressource en ligne; sciences; sciences humaines; systèmes d'oppressions; thématiques; travail; travail scientifique; épistémologie

Save Yourself - Esposito, Cameron (Grand Central Publishing, 2020)
This "hilarious and honest" bestselling memoir from a rising comedy star tackles issues of gender, sexuality, feminism, and the Catholic childhood that prepared her for a career as an outspoken lesbian comedian (Abby Wambach).Cameron Esposito wanted to be a priest and ended up a stand-up comic. Now she would like to tell the whole queer as hell story. Her story. Not the sidebar to a straight person's rebirth-she doesn't give a makeover or plan a wedding or get a couple back together. This isn't a queer tragedy. She doesn't die at the end of this book, having finally decided to kiss the girl. It's the sexy, honest, bumpy, and triumphant dyke's tale her younger, wasn't-allowed-to-watch-Ellen self needed to read. Because there was a long time when she thought she wouldn't make it. Not as a comic, but as a human. SAVE YOURSELF is full of funny and insightful recollections about everything from coming out (at a Catholic college where sexual orientation wasn't in the nondiscrimination policy) to how joining the circus can help you become a better comic (so much nudity) to accepting yourself for who you are-even if you're, say, a bowl cut-sporting, bespectacled, gender-nonconforming child with an eye patch (which Cameron was). Packed with heart, humor, and cringeworthy stories anyone who has gone through puberty, fallen in love, started a career, or had period sex in Rome can relate to, Cameron's memoir is for that timid, fenced-in kid in all of us-and the fearless stand-up yearning to break free.
Keywords: amériques; approches et analyses; corps; humour; identités LGBTQIA2+; personnes lesbiennes; privilèges; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; travail; états-unis

Intersectionality in feminist and queer movements: Confronting privileges - Evans, Elizabeth; Lépinard, Éléonore (Routledge, 2020)
Examining the ways in which feminist and queer activists confront privilege through the use of intersectionality, this edited collection presents empirical case studies from around the world to consider how intersectionality has been taken up (or indeed contested) by activists in order to expose and resist privilege. The volume sets out three key ways in which intersectionality operates within feminist and queer movements: it is used as a collective identity, as a strategy for forming coalitions, and as a repertoire for inclusivity. The case studies presented in this book then evaluate the extent to which some, or all, of these types of intersectional activism are used to confront manifestations of privilege. Drawing upon a wide range of cases from across time and space, this volume explores the difficulties with which activists often grapple when it comes to translating the desire for intersectionality into a praxis which confronts privilege. Addressing inter-related and politically relevant questions concerning how we apply and theorise intersectionality in our studies of feminist and queer movements, this timely edited collection will be of interest to students and scholars from across the social sciences and humanities with an interest in gender and feminism, LGBT+ and queer studies, and social movement studies.
Keywords: LGBTQIA2+; approches et analyses; identités LGBTQIA2+; intersectionnalité; militance; outils; ouvrages de références; privilèges; queer; ressource en ligne; systèmes d'oppressions; thématiques

Collectiviser la question parentale: les apports des parenting cultures studies - Martin, Claude (Lien social et Politiques, 2020)
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; care; cours; discipline; europe; france; justice sociale; maternité; parentalité; patriarcat; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques